Laser processing of Ti6Al4V alloy: wetting state of surface and environmental dust effects. Issue 2 (February 2019) - Yilbas, B.S.; Ali, H.; Al-Sharafi, A.; Al-Qahtani, H.
Abstract: Laser processing of Ti6Al4V alloy surface, via repetitive pulses, is realized incorporating the nitrogen assisting gas. The texture characteristics of the surface and wetting state are analyzed. The free energy of the laser treated surface is estimated. The influence of the dust particles on the treated and untreated surfaces is examined. The solution formed due to water condensate on the dust particles is evaluated. The adhesion of the mud dried solution on the treated and untreated surfaces is assessed through determining the tangential force required for the removal of the solution from the surface. The findings demonstrate that the high power laser repetitive pulse heating results in formation of the hieratically distributed micro/nano pillars on the workpiece surface. The wetting state of the processed surface remains hydrophilic because of the large gap size between the micro/nano pillars. The free energy of the laser textured surface is similar to that obtained for the TiN coated surfaces, which is because of the nitride compounds developed during the processing. The dried liquid solution strongly adheres at the surface and the force needed for removing the dried liquid solution is almost four times of the friction force at the surface. The liquid solution gives rise to locally scattered shallow pit sites on as received surface. This phenomenon does not occur for the laser treated surface, which is related to the passive layer developed on the surface.